Implementasi Sistem Aplikasi Pengelolaan Hibah Terintegrasi dalam Rangka Meningkatkan Good Governance - Safuan, Safuan; Mardiana, Tina (Program Studi Teknik Informatika Universitas Pamulang, 2023)
The State Ministry/Institutions receiving the grant is required to administer the grant management to the Ministry of Finance as the State General Treasurer. Central government grant management administration is carried out through several stages, from the registration process to the accountability process. Grant registration stages are carried out manually by sending registration application documents to the Ministry of Finance via expedition services. In addition, each administrative stage of grant management uses several different applications managed by each authorized echelon I unit in the Ministry of Finance. This causes the administrative process of grant management to take a long time, is inefficient, and affects the accountability of financial reports due to differences in data/information generated by each application. To overcome this, digitization of the grant registration business process is needed, and integration of grant data/information from several applications used. The application development method uses the Waterfall System Development Life Cycle (SDLC) with the Oracle database. The framework used is .NET (dotnet) Core as the back end (C# language), and Angular as the front end (typescript language). The system development design using the intended method can produce an application that can increase the effectiveness and efficiency of the grant registration process, and integrate data/information from several applications in order to realize good governance.